Large-scale fabrication of nanostructure on bio-metallic substrate for surface enhanced raman and fluorescence scattering - Lu, Libin (2019)
The integration of surface-enhanced Raman scattering (SERS) and surface-enhanced fluorescence (SEF) has attracted increasing interest and is highly probable to improve the sensitivity and reproducibility of spectroscopic investigations in biomedical fields. In this work, dual-mode SERS and SEF hierarchical structures have been developed on a single bio-metallic substrate. The hierarchical structure was composed of micro-grooves, nano-particles, and nano-ripples. The crystal violet was selected as reporter molecule and both the intensity of Raman and fluorescence signals were enhanced because of the dual-mode SERS−SEF phenomena with enhancement factors (EFs) of 7.85 × 105 and 14.32, respectively. The Raman and fluorescence signals also exhibited good uniformity with the relative standard deviation value of 2.46% and 5.15%, respectively. Moreover, the substrate exhibited high sensitivity with the limits of detection (LOD) as low as 1 × 10−11 mol/L using Raman spectroscopy and 1 × 10−10 mol/L by fluorescence spectroscopy. The combined effect of surface plasmon resonance and “hot spots” induced by the hierarchical laser induced periodical surface structures (LIPSS) was mainly contributed to the enhancement of Raman and fluorescence signal. We propose that the integration of SERS and SEF in a single bio-metallic substrate is promising to improve the sensitivity and reproducibility of detection in biomedical investigations.